2020
DOI: 10.3390/microorganisms8091296
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Promotion of Peppers (Capsicum annuum L.) by Trichoderma guizhouense NJAU4742-Based Biological Organic Fertilizer: Possible Role of Increasing Nutrient Availabilities

Abstract: Trichoderma spp. is a cosmopolitan group of soil fungi which plays a remarkable role in stimulating plant growth after interacting with plant roots and has good application prospects in intensive agriculture. In this study, rice straw and amino acids improved the population of Trichoderma guizhouense NJAU4742 under solid-state fermentation and helped us develop a new type of organic fertilizer. The effects of this biological organic fertilizer were evaluated in the growth of peppers (Capsicum annuum L.) for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 56 publications
(40 reference statements)
2
10
0
1
Order By: Relevance
“…Generally, higher biomass weights were found in the organic amendments with vermicompost and biochar whereas lower values were weighed in the control treatment and conventional composts during direct application and residual effects, possibly due to the significant variation in growth media physicochemical properties, such as organic carbon, total nitrogen content, and bulk density which led to increasing fresh biomass weight by improving soil fertility and nutrient uptake capacity [36]. is result was in agreement with several research findings [7,[76][77][78][79][80], who concisely reported that there is an increment in total plant fresh biomass weight when organic fertilizer specially vermicompost or biochar is applied. e advancing trend of pepper total biomass was mainly for the account of the increased mass of the above and underground organs [82].…”
Section: Total Fresh Biomass Weight (G)supporting
confidence: 90%
“…Generally, higher biomass weights were found in the organic amendments with vermicompost and biochar whereas lower values were weighed in the control treatment and conventional composts during direct application and residual effects, possibly due to the significant variation in growth media physicochemical properties, such as organic carbon, total nitrogen content, and bulk density which led to increasing fresh biomass weight by improving soil fertility and nutrient uptake capacity [36]. is result was in agreement with several research findings [7,[76][77][78][79][80], who concisely reported that there is an increment in total plant fresh biomass weight when organic fertilizer specially vermicompost or biochar is applied. e advancing trend of pepper total biomass was mainly for the account of the increased mass of the above and underground organs [82].…”
Section: Total Fresh Biomass Weight (G)supporting
confidence: 90%
“…Regarding soil activity of the fungus, the association with soil minerals and the solubilization of phosphate is a well-known process that is carried out by Trichoderma fungi and highlights the promotion of mobility of this important macronutrient for plants [ 65 ]. The moderation of nitrogen and carbon concentration in the soil and the plant, along with Fe 3+ chelating siderophores production, is a process that leads to increased nutrient availability [ 66 ]. However, there are also reports about potential negative effects on the crop due to the production of phytotoxic metabolites (trichothecenes) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation process was carried out for 40 days, which is an optimal period according to previous studies [30]. Fermentation has been reported to potentially increase nutrient availabilities in certain fertilizers [31]. However, there remains limited information regarding the beneficial effects of fermentation on chemical components of seaweed biomass-based fertilizers.…”
Section: Fermented Fertilizer Productionmentioning
confidence: 99%